Is holistic focus of attention equally effective to external focus in performing accuracy of table tennis forehand stroke in low-skilled players? - Weronika Łuba-Arnista; Paweł Arnista; Tomasz Niźnikowski; Jerzy Sadowski; Andrzej Mastalerz; Wojciech Ratkowski; Ewelina Niźnikowska; Paweł Różański; Marcin Starzak (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background The holistic focus of attention due to promising motor learning and performance benefits constitutes an desired direction for scientific investigations in sports settings. However, the generalizability of its effect on various motor skills in table tennis requires further investigation. The study aimed to determine the impact of holistic focus of attention and proximal and distal external focus on the accuracy of the table tennis forehand stroke in low-skilled players. Methods Eighty undergraduate physical education students were randomly assigned one of four groups: focus on the ball (GPEF, n = 20), focus on targets marked on the tennis table (GDEF, n = 20), focus on feeling smooth and fluid when playing (GHF, n = 20), and control group was subjected to none of the experimental factors (CNTRL, n = 20). The participant’s task was to score as many points as possible by hitting the ball using the forehand technique in table tennis inside the three smallest targets marked on the tennis table. The data were analysed using one-way ANOVA and mixed-ANOVAs with repeated measures on the last factor. Post-hoc pairwise comparisons (Fisher LSD test) were conducted to estimate the statistical significance of the intra-differences between the results. Partial Eta squared and Cohen’s d were calculated to estimate effect size. Results The highest improvement of score results was observed in the group with focus on feeling smooth and fluid when playing, while the lowest was observed in the group with focus on the ball both on the post-test and delayed retention test. Nevertheless, each group significantly improved their score results on the post-test and the delayed retention test, which indicates that holistic focus, proximal and distal external focus, had similar effects on the accuracy of the table tennis forehand stroke in low-skilled players. Conclusions The study found that holistic focus and proximal and distal external focus are equally effective in improving the accuracy of the table tennis forehand stroke for players with lower skill levels. We recommend that coaches and practitioners use holistic and external attentional focus cues to enhance motor skill performance in table tennis. For example, when teaching or improving the table tennis strokes, coaches can apply a holistic cue like “focus on smoothing out your wrist movement” or an external cue like “focus on the target area of the table”.